13- STUDY THE EFFECT OF DIFFERENT CULTURE MEDIA ON SOME FROZEN SEMEN CHARACTERISTICS OF IRAQI BLACK LOCAL GOAT SPERMATOZOA - Taher A.Fahad; Khairi G. Al-Rikabi; Abdulrazak N. Khudair (Basrah Journal of Veterinary Research)
The semen was collected from five adult Iraqi black local bucks by the artificial vagina and using estrous induced doe the semen was diluted with egg yolk 10% extender and frozen by liquid nitrogen for three months, macroscopic and microscopic evaluation were done after collection, dilution and thawing, three media(TCM-199, DMEM and SOF)were used to see the their effect on activation of spermatozoa. The results showed that TCM-199 media presented higher significance in sperm motility, progressive motility compared with DMEM and SOF media. There was a great decrease in the concentration of spermatozoa after activation using these media which didn’t differ significantly among them and they were higher significantly compared with control in normal morphology.